Expert Consensus on the Management of Acute Otitis Media in India: A Delphi Study - Tanu Singhal; Shyam Kukreja; Jaydeep Choudhury; Vijay Yewale; Balasubramanian Sundaram; Jagdish Chinnappa; Suhas Prabhu; Balaji Veeraraghavan; Camilla Rodrigues; Vidya Krishna; Winsley Rose; Samir Bhargava (Pediatric Infectious Disease)
Aim and background: Acute otitis media (AOM) and otitis media with effusion (OME) are common childhood ear infections. The changing epidemiological landscape in India and growing concerns about antimicrobial resistance underscore the need for evidence-based, updated guidance on management. This expert consensus using the Delphi methodology was undertaken to deliberate and consolidate statements to guide the management of AOM and OME in India. Methods: A panel of 12 experts comprising pediatric infectious disease specialists, clinical microbiologists, and ear, nose, and throat (ENT) specialists participated in a three-step modified Delphi study conducted between April 2023 and January 2024. Overall, 101 statements were derived from an extensive literature search and shared with the experts for their response in the form of “yes” or “no” during round 1. Statements lacking consensus (predefined as <80% agreement) in round 1 were reevaluated in round 2, following a similar process for reaching consensus. Statements pending consensus in round 2 were then discussed in a virtual meeting (round 3). Results: A total of 83/101 (82.2%) statements in round 1 and 15/18 (83.33%) statements in round 2 achieved consensus (≥80% agreement) among the experts. A few statements were revised and updated based on the inputs from the experts, and 23 statements were deliberated in the virtual discussion during round 3. Finally, experts agreed to include 67 statements pertaining to risk factors, resistant strains, conservative and symptomatic management, and antibiotic treatment algorithms for AOM and OME. Conclusion: The consensus recommendations provide systematic guidance to clinicians on the appropriate management of AOM and OME. Clinical significance: These recommendations encompass stepwise interventions and address initial treatment as well as potential scenarios of treatment failure or recurrence in AOM and OME.